Numerical simulation analysis of the induced thrust on a char particle in reaction process. Issue 7 (11th April 2022) - Zhou, Shengyu; Shen, Zhongjie; Liang, Qinfeng; Xu, Jianliang; Dai, Zhenghua; Liu, Haifeng
Abstract: The force exerted on particles is of great significance to the flow and reaction characteristics of particles in gasifier. In this study, the unbalanced thrust, especially its magnitude, of a single char particle induced by chemical reactions during combustion process is investigated numerically, based on the random distribution of active sites. It is revealed that the nonuniform distribution of active sites directly leads to the nonuniform absorption of reactants and release of products, which accounts for the net induced thrust on particles. The effects of active site ratio, ambient gas temperature and particle diameter on the induced thrust of reacting particles were investigated. The results show that the induced thrust on particles could be equal to the magnitude of particle gravity. The induced thrust is determined by the nonuniformity of carbon distribution on char surface. The net thrust is enhanced with the increase of specific carbon consumption rate.